Dekonstruksi Media Massa Atas Peran Perempuan: Upaya Pemberitaan Sensitif Gender - Waid, Abdul (Musawa Jurnal Studi Gender dan Islam, 2007)
Most people don't realize that recently mass media has been discrediting women. News about women by media displays them purely on physical appearance as though it had been an "image" for a woman. The most tragic fact is that the language used in mass media merely focuses on physical appearance. This fact is indicated by a huge "show" by mass media that only display women as a commodity. Indirectly, mass media have exploited women for their own interests; namely increase their ratings (for TV) and tiras (for printed press). Displaying women merely as an object can be regarded as a crime, but it happens both in the news and infotainment."Psikologi perempuan juga psikologi massa, hendaknya dipahami oleh para bapak yang kebanyakan menjadi penentu kebijakan. Bila rncsszr ada yang diperlakukan kurang adil, lebih-lebih itu mengenai perempuan, tanpa dimintapun bangkit perasaannya". Titie Said (Psikolog), 1999.